EXPERIMENTS ON RHEOLOGY OF NON-NEWTONIAN FLOW OF TYLOSE-ALGINATE SUSPENSION THROUGH A HORIZONTAL COMPLEX CONDUIT - FAGLA, Benoît Fanou Zinsou; GRADECK, Michel; LEBOUCHE, Michel (My University, 2013)
Experiments were conducted on rheological behavior of pseudoplastic non-Newtonian tylose-alginate (solidliquid) suspensions in isothermal laminar flow in a horizontal conduit with variable geometry. The complex flow of loaded spherical and large-sized particles of 4.4 mm diameter, and dependence of hydrodynamics of organoleptic quality of the loaded fluids governed by Ostwald power law were investigated. The geometry of the horizontal pipe of variable cross-section provided turbulence promoters for fluid flow which generated backflow zones for homogenizing the suspensions by improved mixing quality. The consistency index (K) increased with the volume fraction of solid particles, but decreased with temperature; and for a net change in viscosity of 0.75 % tylose concentrated solution, K increased with temperature of the carrier fluid. The structure index, n, varied with the concentration of the hard spheres, but did not vary substantially with temperature.
Keywords: Rheological behavior; Tylose-Alginate flow suspensions